Analisis Komparasi Investasi Dinar dan Investasi Reksadana Pasar Uang Syariah - Feriyani, Nur Ayu Eva (Al-Iqtishad: Journal of Islamic Economics, 2013)
The aim of this study is to analyze return and risk in Dinar investment and shariah money market mutual funds which resultd from movement price dinar and NAB sharia money market mutual fund at period of January 2008 until December 2012. The study used t-test that resulted of expected return dinar equal to 1,56% while sharia money market mutual fund equal to 55,6%. Based on the analyses of return sharia money market mutual fund better than Dinar, however shariah money market mutual fund has significant higher than DinarDOI: 10.15408/aiq.v5i2.2125